Signature of Oxide-Ion Conduction in Alkaline-Earth-Metal-Doped Y3GaO6 - Singh, P.; Pandey, R.; Miruszewski, T.; Dzierzgowski, K.; Mielewczyk-Gryn, A.; Singh, P. (American Chemical Society, 2020)
We have studied alkaline-earth-metal-doped Y3GaO6 as a new family of oxide-ion conductor. Solid solutions of Y3GaO6 and 2% -Ca2+-, -Sr2+-, and -Ba2+-doped Y3GaO6, i.e., Y(3-0.06)M0.06GaO6-δ (M = Ca2+, Sr2+, and Ba2+), were prepared via a conventional solid-state reaction route. X-ray Rietveld refined diffractograms of all the compositions showed the formation of an orthorhombic structure having the Cmc21 space group. Scanning electron microscopy (SEM) images revealed that the substitution of alkaline-earth metal ions promotes grain growth. Aliovalent doping of Ca2+, Sr2+, and Ba2+ enhanced the conductivity by increasing the oxygen vacancy concentration. However, among all of the studied dopants, 2% Ca2+-doped Y3GaO6 was found to be more effective in increasing the ionic conductivity as ionic radii mismatch is minimum for Y3+/Ca2+. The total conductivity of 2% Ca-doped Y3GaO6 composition calculated using the complex impedance plot was found to be ∼0.14 × 10-3 S cm-1 at 700 °C, which is comparable to many other reported solid electrolytes at the same temperature, making it a potential candidate for future electrolyte material for solid oxide fuel cells (SOFCs). Total electrical conductivity measurement as a function of oxygen partial pressure suggests dominating oxide-ion conduction in a wide range of oxygen partial pressure (ca. 10-20-10-4 atm). The oxygen-ion transport is attributed to the presence of oxygen vacancies that arise from doping and conducting oxide-ion layers of one, two-, or three-dimensional channels within the crystal structure. The oxide-ion migration pathways were analyzed by the bond valence site energy (BVSE)-based approach. Photoluminescence analysis, dilatometry, Fourier transform infrared (FTIR) spectroscopy, and scanning electron microscopy studies were also performed to verify the experimental findings. ©
Keywords: Conduction; Alkaline-Earth-Metal-Doped